A review of chloride transport in alkali-activated cement paste, mortar, and concrete. (20th October 2018) - Osio-Norgaard, Jorge; Gevaudan, Juan Pablo; Srubar, Wil V.
Highlights: A review and statistical meta-analysis of chloride transport in AACs is presented. The role of Ca 2+ in glassy/non-glassy phases within precursors is elucidated. Higher Si:Al, Na:Al, and heat-curing, in general, improve chloride resistance. Limitations of current chloride transport measurement techniques are addressed. Research needs concerning chloride durability of AACs are identified and discussed. Abstract: In this review, we present a meta-analysis of experimental data concerning chloride transport in alkali-activated cement (AAC) paste, mortar, and concrete. Sixty-six (66) studies were reviewed with a primary focus on measurement methodology, mixture design, and process-structure-property relationships related to microstructural development (i.e., porosity, pore size distribution), chloride diffusion, and chloride binding. In general, this review elucidates that aluminosilicate precursors with high amorphous contents and increased fineness that are activated with solutions of high alkalinity (Na:Al ≥ 0.75) and silica content (Si:Al ≥ 1.5) in combination with heat-curing (>40 °C) lead to microstructural characteristics (e.g., binder gel chemistries) that improve chloride durability, even though interactions between these factors are not well understood. Descriptive statistics of reported AAC paste porosities and AAC concrete chloride diffusion coefficients by aluminosilicate precursor (i.e., fly ash, slag, calcined clay, natural clay, binary blends) are presented, along with a summative discussion regarding new opportunities for advancing current scientific understanding of chloride transport in AACs.